​​Fatigue Life Enhancement of Metallic Aircraft Structures Using Bonded Crack Retarders - A Finite Element Study with VCCT and Cohesive Surface in ABAQUS​ - ​​Sajnani​, Dhaval Rameshkumar (Cranfield University, 2025)
​​This research investigates the fatigue life enhancement of aluminium structures through the application of bonded crack retarders, modelled and analysed using the finite element (FE) method in ABAQUS. The study focuses on an aluminium plate specimen with centrally located cracks, reinforced symmetrically on both surfaces by bonded crack retarders, aiming to delay crack propagation and extend structural service life. The FE model incorporates advanced fracture mechanics techniques, including the Virtual Crack Closure Technique (VCCT) and the Cohesive Surface, to accurately simulate crack initiation and growth under cyclic loading. From these simulations, the strain energy release rate (SERR) components are extracted and utilised to compute stress intensity factors (SIFs). These SIF values form the basis for fatigue life prediction, performed through AFGROW simulations. The computational results are rigorously compared against previously conducted experimental data to assess model fidelity and predictive accuracy. The outcomes of this study contribute to the understanding of bonded crack retarder performance and provide a validated numerical framework for fatigue life estimation in aerospace grade aluminium components.​
Keywords: atigue analysis; FEA; ABAQUS; VCCT; CZM; Cohesive Surface; Crack Propagation; Damage Tolerance; BCR; Bonded Crack retarders